Idiopathic pulmonary fibrosis - novel approach on future treatment - Pacek, Katarzyna; Piekarska, Małgorzata; Pikulicka, Agata; Jedlina, Klaudia; Szulc, Izabela; Kasperski, Radosław; Swacha, Weronika; Makowska, Karolina (Journal of Education, Health and Sport, 2023)
Introduction Idiopathic pulmonary fibrosis (IPF) is a fatal pulmonary disease that leads to progressive fibrosis and extremely poor resaults.. Since the etiology is unknown, there are highly limited options of the IPF treatment. The researchers are trying to discover the most valuable targets, leading them to the agents registered in different conditions or not registered as any other treatment. This innovative approach can result in IPF being determined as not fatal. Purpose The purpose of our review is to present possible future treatment of idiopathic pulmonary fibrosis and point out the promising targets that could lead the researchers to the development of better IPF management. Materials and methods We have reviewed the literature from the PubMed database searching for clinical trials, meta analysis and randomized controlled trials from the past 5 years. The keywords we agreed on offered us the most informative articles and made us hope for the further development of our article. Results Our review shows that there are new targets that could significantly benefit IPF treatment. However, the means we presented in our review need more research to prove its safeness, effectiveness in slowing down the decline of the FVC, improving patients’ physical efficiency, their saturation level and most importantly their ability to stop the continuous fibrosis of the lungs. Conclusions The only treatment registered for IPF are nintedanib and pirfenidone, but the researchers continue the exploration of new possible measures to improve the survival rate and quality of life of the patients suffering from this fatal disease.